Properties of Active Carbon Derived from Arabica Coffee Pulp and Parchment using Hard Template Method - Pane, Pina Andriani; Setiawan, Adi; Islami, Nurul; Sayuti, M.; Putra, Reza; Hasibuan, Rizqon (Talenta Publisher, 2025)
Utilization of coffee residues such as pulp and parchment into activated carbon provides an alternative approach to electrodes in supercapacitors. The hard template method is used because of its ability to produce a more regular pore structure and higher surface area, which is very important for supercapacitor applications. This research aims to study the effect of template and activation temperature on the characteristics of coffee pulp and parchment using the hard template method. The synthesis process involves carbonization, templating with silica, and activation under nitrogen atmosphere at different temperatures. The resulting materials were characterized to evaluate their structural, surface, and electrochemical properties. The results obtained that higher activation temperature enhances surface area and electrochemical performance, indicating the potential of coffee-based activated carbon as an electrode material for supercapacitors